PENENTUAN PRODUK UNGGULAN DAERAH PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA KUPANG DENGAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) - Letelay, Kornelis; Pandie, E.S.Y; Sabuna, Lidia (Politeknik Negeri Sriwijaya, 2022)
Superior product are one of the things that concern an area in the local revenues, therefore, in determining the superior product herewith the goal is to build a decision support system by applying simple multi attribute rating technique. SMART is a multi- criteria decision making method. This multi-criteria decision-making technique is based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important the criterion is compared to other criteria. This weighting is used to assess each alternative in order to obtain the best alternative. In this study, sensitivity testing was also used to measure the level of weight sensitivity of the criteria for business units, labor, investment value and production value. From the results of sensitivity testing using 62 superior product data on each tested weighting criterion whose weights are increased by 0.5 and 1, the criterion that has the highest sensitivity level or in other words has experienced more changes in ranking is the criteria for investment value with a percentage. Amounting to 95.16% for the addition of the initial weight with 0.5 and 96.77% for the addition of the initial weight by 1.